Association of left ventricular end‐diastolic pressure with mortality in patients undergoing percutaneous coronary intervention for acute coronary syndromes. Issue 4 (6th March 2020) - Leistner, David M.; Dietrich, Steven; Erbay, Aslihan; Steiner, Julia; Abdelwahed, Youssef; Siegrist, Patrick T.; Schindler, Matthias; Skurk, Carsten; Haghikia, Arash; Sinning, David; Riedel, Matthias; Landmesser, Ulf; et al.
Abstract: Objectives: This study sought to investigate the relation between left ventricular end‐diastolic pressure (LVEDP) and outcomes in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndromes (ACS). Background: Risk stratification in ACS patients is important. Data on the role of LVEDP in the prognostication of ACS patients are scarce. Methods: A total of 1, 410 patients undergoing PCI for ACS and with available data on LVEDP were divided according to LVEDP tertiles (lowest tertile: ≤13 mmHg, intermediate tertile: 14–20 mmHg, and highest tertile: >20 mmHg). The primary endpoint was all‐cause mortality at a median follow‐up of 246 [28–848] days. Results: Median LVEDP was 16 (11–22) mmHg. All‐cause mortality was 2.8%, 4.5%, and 15.0% in the lowest, the intermediate, and the highest LVEDP tertile groups ( p  < .001), respectively. Belonging to the highest LVEDP tertile was associated with an increased risk of all‐cause mortality (adjusted hazard ratio [HR] = 2.66, 95% confidence interval [CI] [1.30, 5.47], p = .008). By receiver operating characteristic curve analysis, the optimal cut‐off value for predicting all‐cause mortality was 20 mmHg (sensitivity 68.3%, specificity 72.5%). There was no differential effect of LVEDP on mortality in patients with and without LV dysfunction (interaction p = .23) or ST‐elevation myocardial infarction as index ACS event (interaction p = .86). Conclusions: In patients undergoing PCI for ACS, LVEDP was independently related with mortality. Hence, LVEDP should be incorporated into early risk stratification and clinical decision making of ACS patients.